2018
DOI: 10.1016/j.otsr.2017.08.019
|View full text |Cite
|
Sign up to set email alerts
|

Results and complications of superficialis-to-profundus tendon transfer in brain-damaged patients, a series of 26 patients

Abstract: IV-retrospective or historical series.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 12 publications
0
14
0
Order By: Relevance
“…We included a distal tenotomy of the lumbrical tendons to the index and middle fingers to prevent future overactivity in the median innervated lumbricals. This comprehensive surgical approach to spasticity in the wrist and fingers precludes recurrence of severe deformity as shown in two publications of 31 patients with a mean follow-up of 50 months (Keenan et al., 1987) and 26 patients over 47 months (Peraut et al., 2018). In our series, none of the five patients with a clinical follow-up of over 2 years showed recurrent deformity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We included a distal tenotomy of the lumbrical tendons to the index and middle fingers to prevent future overactivity in the median innervated lumbricals. This comprehensive surgical approach to spasticity in the wrist and fingers precludes recurrence of severe deformity as shown in two publications of 31 patients with a mean follow-up of 50 months (Keenan et al., 1987) and 26 patients over 47 months (Peraut et al., 2018). In our series, none of the five patients with a clinical follow-up of over 2 years showed recurrent deformity.…”
Section: Discussionmentioning
confidence: 99%
“…Previous publications have shown the long-term benefit of upper limb surgery in severe spasticity, mostly with regards to function, appearance or hygiene (Heijnen et al., 2008; Keenan et al., 1987; Peraut et al., 2018; Pomerance and Keenan, 1996; Thevenin-Lemoine et al., 2013). The patients we treated were in the worst group of the Keenan classification (Keenan et al., 1987) for hand position and would have been rated as 0 (=does not use hand) in the functional classification of House et al.…”
Section: Discussionmentioning
confidence: 99%
“…Many articles suggest tendon transfer to enhance function or to ease the care in spastic hands. Transfer of the FDS tendon to the FDP is one of the most common techniques (38)(39)(40)(41). Keenan et al (38) reported full accomplishment of goals after the procedure in 34 clenched-fist which were hand open position with the resolution of hygienic problems of palmar skin.…”
Section: Wrist and Fingermentioning
confidence: 99%
“…The comprehensive approach to shoulder, elbow, wrist motor tenotomy with fusion, adequate lengthening of the finger flexors, neurotomy of the deep branch of the ulnar nerve with or without intrinsic release, neurotomy of the recurrent branch of the median nerve with or without release of the thumb adductor, as well as correction of interphalangeal joint deformities provide long lasting effects as all structures potentially hindering access for hygiene in the future are addressed. We referenced the relevant publications with longer follow-up using a similar surgical approach (Heijnen et al., 2008; Keenan et al., 1987; Peraut et al., 2018; Pomerance and Keenan, 1996). We decided against recalling our cohort for logistics and cost reasons.…”
Section: Replymentioning
confidence: 99%